Kuliah Kerja Nyata : Pengabdian Kepada Masyarakat Melalui Pelatihan Pembuatan Sabun Cuci Piring dari Daun Sirih yang Bernilai Ekonomis di Desa Kemiri Sidoaro - Alessandra Nancy Wattimena; Daffa Alifio Hartono; Muhammad Ihsan Ath-Thaariq; Putri Stephany Butar Butar; Budi Prabowo (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2024)
Kemiri Village is one of the villages located in Sidoarjo Regency. Most of the people in Kemiri Village work in the agricultural sector and small MSMEs. One of the plants that is often found is the betel plant which grows in people's yards and has not been utilized optimally. The community service program carried out by National Defense Thematic Community Service (KKN) Group 5 Batch 2 UPN Veteran East Java students is a socialization and training program for making dishwashing soap made from betel leaves which is economically valuable. The method used in this service It goes through several stages, namely the preparation stage, implementation stage and evaluation stage. This activity was attended by PKK women from Kemiri Village who were enthusiastic and enthusiastic. The result of this activity is to provide knowledge and skills to residents to be able to utilize existing natural resources optimally so that the potential of betel leaves can be utilized more effectively. This does not rule out the possibility of producing products that have attractive sales potential, thereby creating new economic opportunities and increasing the welfare of the community in Kemiri Village, Sidoarjo.